Localization of the full-thickness cartilage lesions in medial and lateral unicompartmental knee osteoarthritis. - Gulati, A; Chau, R; Beard, D; Price, A; Gill, H; Murray, D (2009)
This study's aim was to determine the patterns of osteoarthritis (OA) in both unicompartmental medial and lateral OA of the knee. Forty patients with medial and 20 with lateral unicompartmental knee osteoarthritis were studied to determine the location of full-thickness cartilage lesions. Intraoperatively, the distance between margins of the lesion and reference lines were measured. The femoral measurements were transposed onto lateral radiographs to determine the relationship between the lesion site and knee flexion angles. Both tibial and femoral lesions were significantly (p < 0.01) more posterior in lateral OA than medial OA. In medial OA, the lesion center was, on average, at 11 degrees (SD 3 degrees) of flexion, whereas in lateral OA, it was at 40 degrees (SD 3 degrees). The smallest medial femoral lesions were near full extension and, as they enlarged, they extended posteriorly. The smallest lateral femoral lesions extended from 20 degrees to 60 degrees flexion. As these lesions enlarged, they extended both anteriorly and posteriorly. There was a well-defined relationship between the site of the lesions and their size, suggesting that they develop and progress in a predictable manner. The relationship was different for medial and lateral OA, suggesting that different mechanical factors are important in initiating the different types of OA. The lesions in medial OA occur in extension, perhaps initiated by events occurring at heel strike. The lesions in lateral OA begin at flexion angles above those occurring during the single leg stance phase of the gait cycle, so activities other than gait are likely to induce lateral OA.